Impact of Free Fire Game Addiction on Participants' Behavior Educate Qualitative Studies in Class V of SDN 45 Kampung Pinang, Lubuk Basung District, Agam District - Lira Sakinah; Jarudin Jarudin; Wira Solina (Universitas Negeri Padang, 2022)
This research is motivated by the presence of students who are addicted to the free fire game. The purpose of this study is to describe: 1) the impact of addiction to free fire games on students is seen from the aspect of lack of time to socialize. 2) The impact of free fire game addiction on students from the aspect of aggressive behavior and acting hard. 3) The impact of free fire game addiction on students is seen from the aspect of doing negative things. 4) the impact of addiction to free fire games on students is seen from the aspect of physical disorders in the eyes. This research uses a qualitative descriptive research approach. The key informant is DPP. Additional informants were teachers and parents. The instrument used is an interview. Meanwhile, data analysis uses data reduction, data presentation, conclusion drawing and verification. Based on the results of the study revealed that: 1) Lack of time to socialize children in general is a social relationship between children with one another, but sometimes in certain situations the child lacks social time with his family where the child is busy with his own activities. 2) Aggressive behavior and acting hard are generally behaviors that are not able to control themselves in carrying out an activity in daily life, but sometimes in certain situations the child can control aggressive behavior and act violently. 3) Doing negative things is generally a behavior that is shown to be excessive from usual behavior such as being emotional and saying dirty things, but sometimes in certain situations the child can control negative behavior or things. 4) Physical disorders in the eyes are generally disorders that occur in the eyes due to addiction to looking at cellphone screens accompanied by playing games on cellphones, but sometimes in certain situations the child can control eye disorders.